Reliability of Electronic Devices at Early Stages of Life Cycle - Stupak, V. (Elektronika ir Elektrotechnika, 2011)
Early stages of existence of electronic devices are considered: design stage and stage of early failures. At the design stage, works on evaluation of reliability of various variants of structure of electronic devices are carried out. At performance of the given works, help data by manufacturers of components are used. The important question is definition of failure rate of components during the moments of time further from time of publication of help data. The method of forecasting of reliability of components is offered. The method considers data by the manufacturer on change of failure rate of components during the moments of time after publication of help data. The stage of early failures of electronic devices is considered. Two models of dependence of failure rate on time for the given stage are analyzed. Methods of estimation of parameters of considered models and method of estimation of conformity of models with statistical data on failures are offered. Models of reliability of electronic devices are nonlinear, the numerical method of finding the parameters of models is therefore considered. The method provides carrying out of computing experiment. Bibl. 9 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.112.6.445